The Context Meaning of Deixis in Maher Zain Selected Songs - Khasanah, Yatul; Rahmat, Hery (Universitas Khairun, 2024)
The deixis and its contextual meaning in the Maher Zains song are discussed in this study. Content analysis was the form of research used in the descriptive qualitative approach of research methodology. This research uses a practical methodology, based on the conceptualization of deixis by Alan Cruse, which includes person, spatial, temporal, social, and discourse deixis. The purpose of the study is to evaluate the various deixis types and its reference meanings through analysis and interpretation of Maher Zain's